معالم التعايش الإسلامي مع أهل الذمة في الأندلس (316ـ-422هـ): Features of Islamic Coexistence With the People of Dhimmah in Andalusia (316-422 Hijrah) - Faraj Murajia Mousa; Abdul Hamid , Faisal @ Ahmad Faisal; Mohd Nor, Mohd Roslan (Journal Al-Muqaddimah, 2024)
This study examines Islamic dealings with Christians, Jews, and other religions during the time of the Umayyad Caliphate in Andalus. It aims to highlight Islamic coexistence with the people of the Dhimmah and to clarify openness with various peoples, races, and religious, sectarian, and sectarian affiliations. While achieving these two goals, it is evident that this study refutes the violation of human rights in Andalusia. The researchers used narrative, critical, and analytical approaches. To clarify historical facts and events, the results of this historical study demonstrate the interconnection between the inhabitants of Andalusia, provided practical professions and industries. for various segments of society, resulting in improving their social conditions. The findings further show that it encourages material gain, and the spread of the culture of social justice and freedom, and the era of the nobility as well as the different classes ended. Therefore, people became equal, and Muslims worked to eliminate the sources of corruption and deviant morals, such as sex, immorality, indulging in pleasures, cheating, lying, usury, alcohol, and sodomy. Hence, this coexistence contributed to bringing together the elements of civilization: energy, strength, space, and time. It also provided will and optimism, and these foundations raised Andalusian society better. Muslims provided the people of the Dhimmah with everything they needed and made them participate in shaping the features of Islamic civilization on the European continent.